نمذجة العلاقة بين التعليم والخصوبة في ســورية باستخدام طريقة التحليل العاملي - الرفاعي عبد الهادي; حمادة عبد الله; بركات شروق (Latakia University Journal - Economic and Legal Sciences Series, 2019)
بغية بناء نماذج رياضية تمثل العلاقة بين التعليم والخصوبة سيتم أولاً دراسة طبيعة العلاقة بين التعليم والخصوبة في سورية، ومن ثم ستُطبق طريقة التحليل العاملي على المتغيرات التعليمية المؤثرة في الخصوبة، بهدف تحديد المتغيرات الفرضية (العوامل) التي تمثل المتغيرات الأصلية أفضل تمثيل، ونتيجة ذلك تم التوصل إلى ثلاثة عوامل تمثل المتغيرات الأصلية وتكون عبارة عن تراكيب خطية في المتغيرات الأصلية، وسيتم الاستفادة من النتائج السابقة في بناء النماذج الرياضية الملائمة لتمثيل العلاقة بين معدلات الخصوبة العمرية والمتغيرات التعليمية الممثلة بالمؤشرات الثلاثة سابقة الذكر، وأخيراً سننهي البحث بعرض أهم النتائج وتقديم بعض التوصيات التي نراها مهمة. To establish the mathematical model, which represents the relationship between fertility rates and Education, we aimed at first to study the relationship between fertility rates and Education in Syria. We then applied one of the important methods of factor analysis (principal components) on Education variables affecting the fertility to determine hypothetical variables (factors) which best represent the original variables. We concluded that the three factors which best represent the original variables and they are linear compositions. We tried to make use of the previous results to establish the appropriate mathematical models, which represent the relationship between different fertility rates and the three indicators mentioned above representing the education variables. Finally, we provide the most important results and suggest some recommendations that we consider important.